Pemetaan Persebaran Tingkat Ekonomi Masyarakat Kecamataan Berbah Menggunakan Heremap - Prayitna, Adiyuda; Ardhana, Yosef Murya Kusuma (Politeknik Indonusa Surakarta, 2021)
The economic condition in a kepanewon area (sub-district) often shows that the livelihoods of residents in an area may be influenced by available resources and socio-economic conditions such as the education level, the number of existing jobs, skills and capital. Berbah Kepanewon is one of the areas which has the same level with sub-district in the Province of the Special Region of Yogyakarta. A total of 15,188 people (50%) of the population of Berbah Subdistrict work as farmers, as many as 8,641 people (28%) work as breeders and the rest are various professions. Farmers in Berbah Sub-district consist of farmers who own rice fields, farmers who work in the fields, and farm laborers. Farmers in Berbah District cultivate various types of livestock such as: cows, buffaloes, goats, chickens, rabbits and others. The number of people in Berbah District who work in the agricultural sector shows that the Berbah District is included in the type of rural community. To improve the economic level of the community and their standard of living, a method is needed to determine the mapping of the economic level of the community. Therefore, the authors develop a mapping system for the distribution of the economic level of the poor by using an information system and mapping using heremap.